2021
DOI: 10.1002/jssc.202100493
|View full text |Cite
|
Sign up to set email alerts
|

Determination of polyhalogenated carbazoles in waters at low nanogram‐per‐liter concentrations with solid‐phase disk extraction

Abstract: Polyhalogenated carbazoles, a class of emerging contaminants with persistence and dioxin-like toxicity, have received increasing attention in recent years. In this study, a simple, rapid, sensitive, and high throughput method based on solidphase disk extraction and gas chromatography-mass spectrometry was described for the determination of polyhalogenated carbazoles in low nanogram-per-liter range in water samples. The proposed solid-phase disk extraction method was initially optimized, and the optimum experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…More than 20 PHCZs have been subsequently identified in sediment, soil, air, water, and biota samples since the first identification of 1368-CCZ in the sediment of Buffalo River, New York. In recent years, PHCZs have been increasingly measured in the marine environment. Studies showed that the most frequently detected PHCZs were 36-CCZ, 3-CCZ, and 36-BCZ in seawater from several regions of China. The most abundant PHCZs in the surface sediment from the Yangtze River estuary and the adjacent East China Sea were 36-CCZ, 3-CCZ, and 36-BCZ, with mean concentrations of 0.62, 0.15, and 0.14 ng/g, respectively . In contrast, the dominant PHCZs in the surface sediment from the northern South China Sea followed the order 36-CCZ (0.03–0.93 ng/g), 36-BCZ (0–1.14 ng/g), and 1368-BCZ (<0.007–0.37 ng/g) .…”
Section: Introductionmentioning
confidence: 99%
“…More than 20 PHCZs have been subsequently identified in sediment, soil, air, water, and biota samples since the first identification of 1368-CCZ in the sediment of Buffalo River, New York. In recent years, PHCZs have been increasingly measured in the marine environment. Studies showed that the most frequently detected PHCZs were 36-CCZ, 3-CCZ, and 36-BCZ in seawater from several regions of China. The most abundant PHCZs in the surface sediment from the Yangtze River estuary and the adjacent East China Sea were 36-CCZ, 3-CCZ, and 36-BCZ, with mean concentrations of 0.62, 0.15, and 0.14 ng/g, respectively . In contrast, the dominant PHCZs in the surface sediment from the northern South China Sea followed the order 36-CCZ (0.03–0.93 ng/g), 36-BCZ (0–1.14 ng/g), and 1368-BCZ (<0.007–0.37 ng/g) .…”
Section: Introductionmentioning
confidence: 99%
“…Some others report better LOD by SPE-RTP with a laborious procedure(0.015) [36], or with SPE-GC-MS, depending on the type of SPE (10 32 and 1 31 ). Also, much lower LOD have been published, for example, based on solid phase disk extraction-GC-MS (0.001) [52], or by a tandem method by UPLC/MS/MS (0.003) [53].…”
Section: Analytical Parametersmentioning
confidence: 99%